Exploring the Use of Claude AI in Reading Comprehension Assessment among Junior High School Students - Febri Yonanda Yovi; Ali Mal Zulfahmi; Febria Sri Artika; Melyann Melani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study described the use of Claude AI as an assessment tool in analysing Junior High School students’ reading comprehension performance. A descriptive research design was employed involving 38 students of SMP Negeri 3 Bukittinggi. Data were collected through a reading comprehension test consisting of one reading passage and five open-ended questions representing four reading indicators: literal comprehension, vocabulary in context, inferential reading, and critical thinking. Students’ responses were assessed using Claude AI and analysed descriptively. The finding showed that students performed strongest in literal comprehension, moderately in vocabulary and inferential reading, and weakest in critical thinking, with an overall average score of 68%. The results suggest that students possess adequate foundational reading skills but require further support in developing higher-order comprehension abilities. Claude AI demonstrated potential for providing rapid assessment and feedback, immediate feedback, and systematic analysis of student responses. However, its ability to evaluate complex reasoning and contextual factors remains limited the study concludes that Claude AI can serve as a useful formative assessment tool when combined with teacher judgement. These findings contribute to the growing discussion of AI-assisted assessment in English Language Teaching activities.